Influence of Human Resource Management on Attainment of Organizational Goal in the University of Jos Library - Shittu Lukman Olayinka; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
This study examined the influence of human resource management on attainment of organizational goal in the university of Jos library. The study was guided by four objectives. Inline with these objectives the study answered four corresponding research questions. The research design employed was a survey research design specifically cross-sectional survey research design. The target population consists of 40 staff of the permanent site library of the University of Jos. The sample size consists of the same number as the population. The instrument used for data collection was a structured questionnaire titled Questionnaire on Influence of human resource management on attainment of organizational goal in the university of Jos library” (QIHRMAOG). The instrument was subjected to face and content validity. The reliability of the instrument was also established at 0.81 coefficient. The data collected was analyzed simple percentage, frequency count, and mean method as well as standard deviation. The analysis revealed that, human resource management positively influences organizational goal attainment in the University of Jos Library and also that effective recruitment policies enhance employee performance and institutional effectiveness among others. The study concluded that, adoption of strategic HRM practices has the potential to foster a productive and innovative work environment, overcoming the systemic obstacles is essential for realizing the full benefits of these initiatives. The study also recommended among other things that, The university management should establish a structured mechanism for continuous evaluation and refinement of HRM practices to ensure they align with the institution’s evolving goals.